Optimalisasi Mekanisme Koping Ibu Dalam Program Pemberian Makanan Tambahan (PMT) Untuk Pencegahan Stunting - Sutiyah Heni (STIKES dan AKZI Karya Husada Kediri, 2024)
There are two types of Supplementary Feeding (PMT), namely recovery Supplementary Feeding (PMT) and Supplementary Feeding (PMT) counseling. Having the same goal is to meet the nutritional needs needed by toddlers. The purpose of community service activities is to provide education on how adaptive coping mechanisms for mothers in the Supplementary Feeding (PMT) program for stunting prevention so that mothers are able to think positively and adapt and find constructive solutions to care for toddlers by fulfilling appropriate nutrition. Education or counseling will be carried out on September 2-October 7, 2023, in the PKM Kepung Working Area, Kediri Regency, East Java. Participants / mothers with toddlers who followed as many as 35 people. The number of students who participated in the activity was 2 students. The method used lectures, discussions / questions and answers with leaflet media, explanation of material using LCD media and laptops. The results of interviews and filling out questionnaires on how to coping mechanisms in mothers in the Supplementary Feeding (PMT) program for stunting prevention found that most respondents had adaptive coping mechanisms and almost half of respondents had maladaptive coping mechanisms. Adaptive coping mechanisms for mothers in supplementary feeding programs (PMT) for stunting prevention can be done by how to improve strategies and how to solve problems by learning from the experience of mothers who have healthy toddlers and always think positively about the condition of their children and believe that their children are healthy toddlers who are not stunted, ask for help from others and seek information and make plans to overcome problems and straighten thoughts or perceptions of problems related to fulfilling toddler nutrition. Health workers and posyandu cadres are expected to provide education and support to mothers in achieving nutritional intake in toddlers by arranging/varying food preparations every day in accordance with 4 healthy 5 to improve coping by carrying out useful activities and activities while caring for toddlers.